Polanyi and the Instituted Processes of Markets: Introducing a Wellbeing Perspective - Johnson, Susan (2009)
Analysis of the role of markets in development is mainly focused on their ability to promote material provisioning. Polanyi argued that markets were only one approach to material provisioning, and that the concept of the self-regulating market had become disembedded from society. He was concerned that processes of provisioning be understood within the wider framework of society and developed the concept of instituted process as a means to understand this role. This paper sets out to explore whether and how Polanyi’s concept of instituted process might work with emerging approaches to analysing wellbeing – what it means to live well – to offer tools for the institutional analysis of markets.
Keywords: embeddedness; instituted economic process; instituted process; institutions; well-being

The Great Transition - Spratt, Stephen; Simms, Andrew; Neitzert, Eva; Collins, Josh-Ryan (New Economics Foundation, 2009)
Maps out a set of solutions to various systemic problems "This report argues that nothing short of a Great Transition to a new economy is necessary and desirable, and also possible. " - We have called the process by which this could happen the Great Transition as a deliberate echo of The Great Transformation, written by Karl Polanyi in the 1940s.1 While in a relatively short report such as this we could not hope to achieve anything remotely comparable to Polanyi’s great work, the scale of the change we need to see is at least the equal of the changes he described. Polanyi analysed how market processes in the industrial revolution had created severe ruptures in the fabric of social life, and argued strongly that we needed to reverse this and nd a balance between the market and the non-market; the private and the public; the individual and the community. We couldn’t agree more, and the need to achieve this is all the more pressing now given the huge environmental problems we face, problems that Polanyi could not have foreseen in 1944 when the world was caught in the bloody conclusions of the Second World War. The most pressing problem facing humanity now is how to share scarce planetary resources in ways that are just, sustainable and support the well-being of us all.
Keywords: environemntal politics; environmental value; redistribution